In vitro gas production and fermentation of dairy cow diet contaminated with glyphosate herbicide - Meeprom, Chayapol; Ampapon, Thiwakorn; Piyadeatsoontorn, Sudthidol; Wattanakornsiri, Amnuay; Thanomsit, Chutima (Agriculture and Natural Resources, 2024)
Importance of the work: Glyphosate is one of the most widely used herbicides in Thailand. However, its residue can interfere with microbial activity. Objectives: To evaluate ruminal degradation and fermentation of microbiota measured using an in vitro gas production technique in different glyphosate-contaminated dairy cow diets. Materials & Methods: A completely randomized design was utilized for the experiment, incorporating six treatments: glyphosate levels of 0.43 mg/kg dry matter (DM), 1.05 mg/kg DM, 2.33 mg/kg DM, 2.98 mg/kg DM, 4.77 mg/kg DM, and 5.54 mg/kg DM in the dairy cow diet. Each treatment comprised five replications. An in vitro gas production technique was used for data collection at various incubation times. Results: None of the levels of glyphosate affected the accumulation of gas production at 8 hr, 12 hr, 24 hr and 48 hr incubation. However, glyphosate at over 2.33 mg/kg DM reduced the accumulated gas production at 72 hr incubation. The lower gas production was due to the insoluble fraction in those diet containing glyphosate at 2.98 mg/kg DM, 4.77 mg/kg DM and 5.54 mg/kg DM. There were no effects on DM degradability at all glyphosate levels at 24 hr, while at 1.05 mg/kg DM, there was a decrease at 48 hr. Values of pH, ammonia nitrogen and total volatile fatty acid decreased when more than 2.33 mg/kg DM glyphosate were added. The higher levels of glyphosate provided greater propionic acid and butyric acid proportions at 12 hr, which were greatest in the diet at 5.54 mg/kg DM. Main finding: A dairy cow diet contaminated with glyphosate at higher than 2.33 mg/kg DM decreased the microbial activities of feed degradation, requiring more ammonia nitrogen to be used for microbial protein synthesis.